2012
DOI: 10.1097/ta.0b013e318241f534
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and injury characteristics in severe open tibia fractures from combat

Abstract: Type III open tibia fractures from combat unite in 80.3% of cases at an average of 9.2 months. We recorded a 27% deep infection rate and a 22% amputation rate. The G/A type is associated with development of deep infection, need for amputation, and time to union. Positive surveillance cultures are associated with development of deep infection, osteomyelitis, and ultimate need for amputation. Surveillance cultures were not predictive of the infecting organism if a deep infection subsequently develops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 26 publications
8
70
1
1
Order By: Relevance
“…16 Majority of S.aureus was isolated from cases of orthopaedic SSI and procedure was open fractures with fixation followed by LSCS surgeries among who underwent emergency procedure. These findings were on par with findings of Burns TC et al 17 However, the incidence of MRSA was significantly higher in our study (37%) when compared with the findings of Burns TC et al, Kamat U et al 18 Various other studies have reported Pseudomonas aeruginosa and Escherichia coli as major isolates in their studies. However, the type of isolate is dependable upon variable physical and operational factors (Type of operation etc.).…”
Section: Discussioncontrasting
confidence: 56%
“…16 Majority of S.aureus was isolated from cases of orthopaedic SSI and procedure was open fractures with fixation followed by LSCS surgeries among who underwent emergency procedure. These findings were on par with findings of Burns TC et al 17 However, the incidence of MRSA was significantly higher in our study (37%) when compared with the findings of Burns TC et al, Kamat U et al 18 Various other studies have reported Pseudomonas aeruginosa and Escherichia coli as major isolates in their studies. However, the type of isolate is dependable upon variable physical and operational factors (Type of operation etc.).…”
Section: Discussioncontrasting
confidence: 56%
“…This finding is relevant given that MRSA is the predominant organism in 35% to 50% of clinically infected combat wounds [3,4]. Often, these wounds demand serial débridements to achieve healthy-appearing and/ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This inability of surveillance cultures to accurately predict the infectious organism has been supported by other studies. [50][51][52][53] While surveillance cultures have limited value in predicting downstream infectious organisms, some studies have suggested a value in surveillance culture bacterial load quantification. This was recently addressed in a retrospective study conducted by Burns et al in a combat environment.…”
Section: Discussion Current Concepts In Open Fracture Care and Infectmentioning
confidence: 99%
“…Other studies have also demonstrated the value of quantifying bacterial loads of wounds for general infection prediction, either through the use of quantitative Gram staining or more commonly through the use of quantitative culturing. [53][54][55][56] The samples used for these bacteria quantifications were either wound swabs, wound effluent, or debrided tissue.…”
Section: Discussion Current Concepts In Open Fracture Care and Infectmentioning
confidence: 99%